2014
DOI: 10.1016/j.exger.2014.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ultrastructure and markers of dynamics in hepatocytes from aged, calorie restricted mice fed with different dietary fats

Abstract: In this paper we analyzed changes in hepatocyte mitochondrial mass and ultrastructure as well as in mitochondrial markers of fission/fusion and biogenesis in mice subjected to 40% calorie restriction (CR) for 18 months versus ad libitum-fed controls. Animals subjected to CR were separated into three groups with different dietary fats: soybean oil (also in controls),fish oil and lard. Therefore, the effect of the dietary fat under CR was studied as well. Our results show that CR induced changes in hepatocyte an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
5
20
1
Order By: Relevance
“…Thus, lard extended longevity compared to soy and fish oils (López‐Domínguez et al ., 2015a) pointing to a role of specific dietary components in determining lifespan of mice fed CR diets. To assess the precise effects of this nutritional intervention at a tissue level, we analyzed the impact of dietary fat in different organs and tissues from animals fed these same diets (see Khraiwesh et al ., 2013 and Khraiwesh et al ., 2014 and López‐Domínguez et al ., 2013, 2015b). In this paper, we studied kidney structure and biology in an attempt to determine the possible role this organ plays in health and aging in CR mice fed diets that differ in fat composition.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, lard extended longevity compared to soy and fish oils (López‐Domínguez et al ., 2015a) pointing to a role of specific dietary components in determining lifespan of mice fed CR diets. To assess the precise effects of this nutritional intervention at a tissue level, we analyzed the impact of dietary fat in different organs and tissues from animals fed these same diets (see Khraiwesh et al ., 2013 and Khraiwesh et al ., 2014 and López‐Domínguez et al ., 2013, 2015b). In this paper, we studied kidney structure and biology in an attempt to determine the possible role this organ plays in health and aging in CR mice fed diets that differ in fat composition.…”
Section: Discussionmentioning
confidence: 98%
“…These results together with those concerning cellular and nuclear size, likely indicate differential adaptation mechanisms to the conditions imposed by CR. Interestingly, the response of PCT cells (in terms of cell and nuclear size and mitochondrial mass) to the different dietary fats under CR described here was similar to that found in mice hepatocytes (Khraiwesh et al ., 2013, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…In mouse hepatocytes we have shown that aging induces a decrease in mitochondrial mass together with reduction in individual mitochondria size and changes in the expression pattern of proteins related to fusion/fission dynamics (Khraiwesh et al, 2014; Khraiwesh et al, 2013; Lopez-Lluch et al, 2006). However, 40% CR alleviated most of these effects by inducing increases in individual mitochondria size and volume fraction occupied by mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial shape also varied with CR in old mice, with more spherical mitochondria being found in all the CR groups regardless of dietary fat. Mean number of cristae per mitochondria and mean crista length were also increased when comparing CR animals with controls and this change was also affected by dietary fat, since a sequential increase in cristal length was found with CR-Soy > CR-Lard > CR-Fish > control (Khraiwesh et al, 2014). These results contrast with those reported in young mice subjected to 6 months of CR where mitochondria of increased size were found only in the CR-Lard group (Khraiwesh et al, 2013).…”
Section: Markers Of Mitochondrial Ultrastructure and Dynamicsmentioning
confidence: 98%
“…Interestingly, the effect of CR on fission proteins was exacerbated by lard and diminished by fish oil, even while liver mitochondria were the largest in CR-Lard compared with the other dietary groups (Khraiwesh et al, 2013). However, these dietary fat-induced differences in markers of mitochondrial dynamics were attenuated by aging (Khraiwesh et al, 2014). …”
Section: Markers Of Mitochondrial Ultrastructure and Dynamicsmentioning
confidence: 99%